(untitled) (Research, Society and Development, 2022)
Objective: To map the care protocols for safe care in hospitalized children. Method: Scope review protocol, registered in Open Science Framework no. osf.io/n6dkv and developed according to Joanna Briggs Institute recommendations, following the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews checklist. The search for articles will be carried out in September 2022, in the MEDLINE, LILACS, PubMed and Scopus databases, and in the theses and dissertations bank of the Coordination for the Improvement of Higher Education Personnel, using Health Science Descriptors and Medical Subject Headings Clinical protocols/ Child/ Hospitalization/ Safety patient and boolean operator AND. The selection will be carried out by two researchers independently. After sampling in the literature, the records will be exported to Rayyan Software, for removal of duplicates and R interface for multidimensional analysis of texts and questionnaires software, for interpretation of results according to similarity analysis, word cloud and textual corpus based on thematic analysis.